2017
DOI: 10.1088/1361-6668/aa757a
|View full text |Cite
|
Sign up to set email alerts
|

MMC-based low-temperature detector system of the AMoRE-Pilot experiment

Abstract: Metallic magnetic calorimeters (MMCs) are highly sensitive temperature sensors that operate at millikelvin temperatures. An energy deposit in a detector can be measured using an MMC through the induced temperature increase. The MMC signal, i.e., a variation in magnetization can then be measured using a superconducting quantum interference device. MMCs are used in particle physics experiments searching for rare processes as their high sensitivity and fast response provide high energy and timing resolutions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The CMO detector assembly is placed in the cryogen-free dilution refrigerator (CFDR) system, which uses a pulse tube refrigerator, providing sufficient cooling power for the system. Performance of the dilution refrigerator confirmed that base temperature of the system reaches below 10 mK and that it has 1.6 µW of cooling power at 10 mK in normal operating condition [13]. In order to isolate the detector system from vibrations of the cryogenic system, R&D has been on-going and possible options were considered such as active damper.…”
Section: Refrigerator and Shieldsmentioning
confidence: 93%
See 1 more Smart Citation
“…The CMO detector assembly is placed in the cryogen-free dilution refrigerator (CFDR) system, which uses a pulse tube refrigerator, providing sufficient cooling power for the system. Performance of the dilution refrigerator confirmed that base temperature of the system reaches below 10 mK and that it has 1.6 µW of cooling power at 10 mK in normal operating condition [13]. In order to isolate the detector system from vibrations of the cryogenic system, R&D has been on-going and possible options were considered such as active damper.…”
Section: Refrigerator and Shieldsmentioning
confidence: 93%
“…The simultaneous measurements of phonon and light signals provide clear separation between α and β /γ events. Detailed principles and designs of detector and sensors are in [4,10,11,12,13]. Recent measurements with prototype detectors during engineering operations showed an energy resolution of 8.7 keV FWHM at 2.6 MeV and clear separations between α and β /γ events [12].…”
Section: Pos(icrc2017)1056mentioning
confidence: 99%
“…The dilution refrigerator system that hosted the AMoRE-Pilot experiment [9,10] has currently been used for its successive AMoRE-I phase with 18 crystal modules and 36 MMC detection channels [11]. The lowest temperature reached 9 mK at the mixing chamber plate (MCP) and detector plate (DP) for this phase.…”
Section: Methodsmentioning
confidence: 99%
“…A persistent current in the superconducting coil generates a magnetic field in the Au:Er sensor material, and energy deposited in the crystal produces a temperature increase in the Au:Er that alters its magnetization. This results in a change in the coil current that is measured by a superconducting quantum interference device (SQUID) [31]. Because of the high sensitivity of the MMC sensors, the detector setup is able to measure precisely the temperature increase resulting from any type of radiation absorption, and particle detection with very high energy resolution is achievable [35,40].…”
Section: For Phonon Detector (At the Back)mentioning
confidence: 99%
“…The advanced molybdenum-based rare process experiment (AMoRE) [28,29] aims to search for 0νββ decay of 100 Mo using a simultaneous heat and scintillation detection technique with crystals operating at mK temperatures. In the present stage of the project, AMoRE-Pilot, calcium molybdate (CaMoO 4 ) crystals are used as the active target elements in a detector concept where the source material is also the detection medium [30][31][32]. The crystals are 100 Mo-enriched and 48 Ca-depleted ( 48depl Ca 100 MoO 4 ).…”
Section: Introductionmentioning
confidence: 99%